2011
DOI: 10.1111/j.1540-8191.2011.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myxomas: Experience Over One Decade

Abstract: Biatrial involvement or multiplicity of myxomas does not mandate recurrence. Surgical excision has excellent overall survival and freedom from reoperation rates, but annual follow-up including echocardiographic surveillance is recommended as familial cases tend to recur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
4
23
0
1
Order By: Relevance
“…Our female/male ratio (14/13) in cardio myxomas differs from that of most other studies, in which this ratio varies from 1.7 to 4.4 : 1 [6, 22], including a large sample from China [7]. Only one Chinese study showed results consistent with ours; in that study, 39 of 75 patients with cardiac myxomas were women [5].…”
Section: Discussionsupporting
confidence: 57%
“…Our female/male ratio (14/13) in cardio myxomas differs from that of most other studies, in which this ratio varies from 1.7 to 4.4 : 1 [6, 22], including a large sample from China [7]. Only one Chinese study showed results consistent with ours; in that study, 39 of 75 patients with cardiac myxomas were women [5].…”
Section: Discussionsupporting
confidence: 57%
“…[13] In another single-center study from India, of 62 patients with the cardiac myxoma, actuarial survival was 96.8 ± 1.8% at 10 years. [14] A study from Pakistan finds agreement with these observations. [15]…”
mentioning
confidence: 62%
“…Of note, embolization and prolapse of the myxoma through valves are more common in polypoid tumours compared to round/oval myxomas (6). …”
Section: Discussionmentioning
confidence: 99%